2015
DOI: 10.1007/s11255-015-1004-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of adiponectin to markers of oxidative stress in type 2 diabetic patients: influence of incipient diabetes-associated kidney disease

Abstract: Adiponectin is a significant predictor of MDA in early diabetic nephropathy, whereas SOD strongly depends only on glycemic control and is not directly related to adiponectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Some papers indicated that the significant increase in MDA levels and decrease in T-AOC levels in early stage of nephropathy in patients with T2D. 21,22 Our results also demonstrated that increase in MDA levels and decrease in T-AOC levels in the renal tissues from 4 weeks DM. The levels of T-AOC and MDA in renal tissues have good line correlations with renal histologic evaluation score, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…Some papers indicated that the significant increase in MDA levels and decrease in T-AOC levels in early stage of nephropathy in patients with T2D. 21,22 Our results also demonstrated that increase in MDA levels and decrease in T-AOC levels in the renal tissues from 4 weeks DM. The levels of T-AOC and MDA in renal tissues have good line correlations with renal histologic evaluation score, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…One study in adipocytes showed that oscillating high glucose exacerbated the suppression of adiponectin mRNA expression and secretion than constant high glucose [8]. Although the protective role of adiponectin against high glucose in various cell lines has been reported [911], its anti-apoptotic mechanism has not been completely understood. Adiponectin exerts anti-apoptotic effect under high glucose condition in HUVECs (human umbilical vein endothelial cells) by activating AMPK [9,12], but very less research has been done in tubular cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore our results do not confirm the assumption that oxidative stress and its resulting damage to DNA are increasing with T2DM progression. Most previous studies compared healthy individuals to T2DM patients and could detect induced oxidative stress in T2DM, represented through decreased FRAP-, GSH- and reduced thiols levels, whereas MDA, oxLDL, GSSG and F2-Isoprostanes were increased [2024, 43, 44]. Additionally, strong linear association to HbA1c was reported for MDA, GSH and oxLDL [20, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding antioxidant enzyme activities of SOD, CAT, GSH-Px, we could not detect any differences between the HbA1c groups. SOD and CAT activity was previously shown to be increased in T2DM compared to healthy controls [20, 43, 46, 47], while GSH-Px was decreased [20, 47]. However, evidence is not sound as some studies could not detect any differences between T2DM and healthy controls in these enzymes [46, 47].…”
Section: Discussionmentioning
confidence: 99%